Mengukur Kontribusi Human Capital terhadap Tujuan Perusahaan - Djojo, Brata Wibawa (Bina Nusantara University, 2010)
Human capital is a valuable asset of any company, especially for competent human resources and contributes both to the company. The performance evaluation given to employees annually can be defined and standardized by the company. However, the question is how big the contribution of human resources to sales and profit contribution is. Case studies take data from one branch of a general insurance company in Indonesia, Jakarta branch. Measurement is done by taking samples of data from 2007, 2008, and 2009. The study measures the risk of several components: (i) Human Capital Revenue Factor, (ii) Human Economic Value Added, (iii) Human Capital Cost Factor, (iv) Human Capital Value Added, and (v) Human Capital Return on Investment. Results of research can provide guidelines for the management, especially for management of JLI in view of Human Capital contribution to corporate objectives, namely in terms of staffing and agency.Â